A pyrexic effect of FGF21 independent of energy expenditure and UCP1 - Petr Zouhar; Petra Janovska; Sara Stanic; Kristina Bardova; Jiri Funda; Blanka Haberlova; Birgitte Andersen; Martin Rossmeisl; Barbara Cannon; Jan Kopecky; Jan Nedergaard (Elsevier, 2021)
Objective: Administration of FGF21 to mice reduces body weight and increases body temperature. The increase in body temperature is generally interpreted as hyperthermia, i.e. a condition secondary to the increase in energy expenditure (heat production). Here, we examine an alternative hypothesis: that FGF21 has a direct pyrexic effect, i.e. FGF21 increases body temperature independently of any effect on energy expenditure. Methods: We studied the effects of FGF21 treatment on body temperature and energy expenditure in high-fat-diet-fed and chow-fed mice exposed acutely to various ambient temperatures, in high-fat diet-fed mice housed at 30 °C (i.e. at thermoneutrality), and in mice lacking uncoupling protein 1 (UCP1). Results: In every model studied, FGF21 increased body temperature, but energy expenditure was increased only in some models. The effect of FGF21 on body temperature was more (not less, as expected in hyperthermia) pronounced at lower ambient temperatures. Effects on body temperature and energy expenditure were temporally distinct (daytime versus nighttime). FGF21 enhanced UCP1 protein content in brown adipose tissue (BAT); there was no measurable UCP1 protein in inguinal brite/beige adipose tissue. FGF21 increased energy expenditure through adrenergic stimulation of BAT. In mice lacking UCP1, FGF21 did not increase energy expenditure but increased body temperature by reducing heat loss, e.g. a reduced tail surface temperature. Conclusion: The effect of FGF21 on body temperature is independent of UCP1 and can be achieved in the absence of any change in energy expenditure. Since elevated body temperature is a primary effect of FGF21 and can be achieved without increasing energy expenditure, only limited body weight-lowering effects of FGF21 may be expected.